Preparation and properties of ferroelectric Pb1-xCaxTiO3 thin films produced by the polymeric precursor method - Pontes, DSL; Leite, E. R.; Pontes, F. M.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Kluwer Academic Publ, 2001)
Pb1- xCaxTiO3 thin films with x = 0.24 composition were prepared by the polymeric precursor method on Pt/Ti/SiO2/Si substrates. The surface morphology and crystal structure, and the ferroelectric and dielectric properties of the films were investigated. X-ray diffraction patterns of the films revealed their polycrystalline nature. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) analyses showed the surface of these thin films to be smooth, dense and crack-free with low surface roughness. The multilayer Pb1-xCaxTO3 thin films were granular in structure with a grain size of approximately 60-70 nm. The dielectric constant and dissipation factor were, respectively, 174 and 0.04 at a 1 kHz frequency. The 600-nm thick film showed a current density leakage in the order of 10(-7) A/cm(2) in an electric field of about 51 kV/cm. The C-V characteristics of perovskite thin films showed normal ferroelectric behavior. The remanent polarization and coercive field for the deposited films were 15 muC/cm(2) and 150 kV/cm, respectively. (C) 2001 Kluwer Academic Publishers.